Physiological and metabolic fluctuations of the diatom Phaeodactylum tricornutum under water scarcity - Hao, Ting-Bin; Lai, Peng-Yu; Shu, Zhan; Liang, Ran; Chen, Zhi-Yun; Huang, Ren-Long; Lu, Yang; Alimujiang, Adili (Frontiers in Microbiology, 2025)
Water scarcity is an escalating environmental concern. The model diatom, Phaeodactylum tricornutum, holds promise as a potential cell factory for the production of high-value natural compounds. However, its dependence on saline water cultivation restricts its use in areas facing water shortages. Although numerous studies have delved into the metabolic mechanisms of plants under water stress, there is a limited understanding when it comes to microalgae. In our study, we employed polyethylene glycol (PEG) to simulate water scarcity conditions, and assessed a range of parameters to elucidate the metabolic responses of P. tricornutum. Water stress induced the generation of reactive oxygen species (ROS), curtailed the photosynthetic growth rate, and amplified lipid content. Our insights shed light on the physiology of P. tricornutum when subjected to water stress, setting the stage for potential applications of microalgae biotechnology in regions grappling with water scarcity.